SOSIALISASI PENGELOLAAN LIMBAH CAIR INDUSTRI BATIK DESA JONO KECAMATAN TEMAYANG KABUPATEN BOJONEGORO - Purwaningrum, Solikhati Indah; Wulandari, Septi; Uswatun K, Winda; Yuliani , Fitria (Jurnal Abdi Masyarakat, 2024)
Mak Nie Batik is one of the Artisanal Small Scale Industry batik in Bojonegoro Regency. Mak Nie Batik has 15 batik craftsmen. This Artisanal Small Scale Industry batik has not received socialization regarding batik liquid waste management so that the Artisanal Small Scale Industry batik has not managed the batik liquid waste produced. In the production process, the batik industry uses a lot of chemicals in the form of dyes and water. Disposal of liquid waste into water bodies causes pollution in the form of: color changes, increasing levels of pH, COD, BOD, TSS, odor and taste changes, obstruction of aquatic biological activity, soil and groundwater pollution, as well as physical changes to plants, animals and humans. This community service project aims to increase craftsmen's understanding of batik industry liquid waste management. This community service uses a participatory approach using focused group discussions in the craftsman community. This community service was carried out smoothly and produced results in the form of increased understanding of craftsmen regarding batik liquid waste management from policy and technology aspects.